ANALISIS SUMBER-SUMBER PEMBIAYAAN PENDIDIKAN DALAM PERSPEKTIF MANAJEMEN PENDIDIKAN - Suyati; Lies Ning Ujiyanti; Siswadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational financing is a crucial component in the implementation of education, playing a significant role in ensuring sustainability and improving educational quality. This study aims to analyze the sources of educational financing and their management from a management perspective. The method used is a literature study with a qualitative descriptive approach by analyzing various scientific references related to educational financing. The results indicate that educational funding sources come from the government, community, private sector/philanthropy, and internal institutional sources. Each source has different characteristics, requiring effective, efficient, transparent, and accountable management. Furthermore, several challenges exist, such as limited funding and low community participation. Therefore, strategies such as diversification of funding sources, strengthening partnerships, and innovation in financial management are necessary. This study is expected to contribute to the development of more optimal educational financial management. Keywords: educational financing, funding sources, educational management, effectiveness, financing strategy